PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS VIII DI SMPIT AL HIJRAH LAUT DENDANG KABUPATEN DELI SERDANG - Fathur Rizqiyah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract :This study aims to determine (1) differences in learning outcomes of Islamic religiouseducation among students who are taught with cooperative learning model type snowball throwingand students taught with conventional learning, (2) differences in learning outcomes of Islamicreligious education students who have high motivation between in teaching with the model of cooperativelearning type snowball throwing and students taught with conventional learning, (3) differencesin learning outcomes of Islamic religious education students who have low motivation betweenin teaching with the model of cooperative learning type snowball throwing and students taught withconventional learning, (4) the interaction between the learning model and the learning motivation onthe learning outcomes of Islamic religious education on students. The design of this research is experimentaldesign. In this study, the experimental group obtained learning by cooperative learning methodof snowball throwing type and control class group by conventional learning. To get the data of researchused instrument in the form of test to know the result of students’ learning and questionnaire of motivationto know students’ motivation in learning Islamic religious Education. This research was conductedat SMPIT AL HIJRAH Laut Dendang, Deli Serdang District, Medan North Sumatera. The sampleis students of class VIII as many as two groups / classes chosen by cluster random sampling technique.Data analysis is done quantitatively. Quantitative analysis was performed on the data of test result to seethe difference of normalized gain score between the sample groups.